Skenario Subsidi Silang (Cross Subsidy) dalam Pembiayaan Sumberdaya Air di Daerah Aliran Sungai (DAS) Kali Brantas - Rahmawati, Farida (Jurnal Aplikasi Manajemen, 2009)
The background of this research is implementation of UU No. 7/2004 about water resources, mention that social users of water resources do not contribute to Biaya Jasa Pengelolaan Sumberdaya Air (BJPSDA). As it concequence, there is limited operational and maintenance cost phenomenon in Brantas River Basin Management from government budget and also from user contribution. The effect is declining of water building function. The aim of the research is to calculate cross subsidy scenario from commercial users (PLN, PDAM, Industry) for social services (irrigation, flood control, water quality). This research serve five alternatives cross subsidy scenario, started from 0 % until 100 % of cross subsidy scenario. To decide the best scenario, it must consider about the willingness to pay and ability to pay of users. Categories of this research is a policy research, because it started from cost problems in Brantas River Basin Management related with implementation of UU No. 7/2004 about water resources.